THE REALITY OF THE GROWTH OF THE OUTPUTS OF THE UNIVERSITY OF BABYLON FROM THE EXPLICIT KNOWLEDGE: ANALYTICAL STATISTICAL STUDY OF THESES COMPLETED BY GRADUATED STUDENTS IN THE PERIOD (1992-2015) - Ramah, Ihsan (Revista Inclusiones, 2019)
The study aims to study the growth of the outputs of the University of Babylon from the Masters and PhD degrees to the colleges of science and technology for the period (1992-2015) through an analytical statistical method and using the law of growth (rate of change). The main conclusions of the study are the following: Master's and doctoral studies at the University of Babylon passed through continuous development processes in the faculties of the university according to the need and the available human, material resources and for most of the university life (1992-2015). Particularly in (2012) and (2015). The period of time (2004-2015) has been much more grown and developed than the period of time (1992-2004) due to the relatively recent age of the university. The most important recommendations were: Establishing the infrastructure of graduated studies at the University of Babylon to be the level of ambition to produce advanced knowledge capital. Activate the knowledge management and knowledge capital at the University of Babylon to be a starting point for access to the knowledge-based economy.